Genotoxic Assessment of Nutraceuticals Obtained from Agricultural Biowaste: Where Do We "AMES"? - Giorgia Musto; Valentina Laurenzi; Giuseppe Annunziata; Ettore Novellino; Mariano Stornaiuolo (MDPI AG, 2022)
Several pharmaceutical companies are nowadays considering the use of agri-food waste as alternative raw material for the extraction of bioactive compounds to include in nutraceuticals and food supplements. This recycling activity is encountering the support of authorities, which are alarmed by air, soil and water pollution generated by agricultural waste disposal. Waste reuse has several economic advantages: (i) its low cost; (ii) its abundance; (iii) the high content of bioactive molecule (antioxidants, minerals, fibers, fatty acids); as well as (iv) the financial support received by governments eager to promote eco-compatible and pollution-reducing practices. While nutraceuticals produced from biowaste are becoming popular, products that have been risk-assessed in terms of safety are quite rare. This despite waste biomass, in virtue of its chemical complexity, could, in many cases, mine the overall safety of the final nutraceutical product. In this review, we summarize the scientific results published on genotoxicity risk-assessment of bioactive compounds extracted from agricultural waste. The review depicts a scenario where the risk-assessment of biowaste derived products is still scarcely diffuse, but when available, it confirms the safety of these products, and lets us envisage their future inclusion in the list of botanicals allowed for formulation intended for human consumption.